Monitoring Ex Situ Electrokinetic Remediation (EKR) using Nitric Acid as Chelating Agent. (January 2020) - Ayuni, S A; Azhar, A T S; Azim, A; Aziman, M
Abstract: Heavy metal has become a serious world crisis due to natural and man-made sources. Zinc contamination in soil is caused by world urbanization and modernization. The Electrokinetic Remediation (EKR) is a green technology aiming at removing zinc contaminated soils. This paper aims to compare the electrokinetic process between Pure System and Nitric acid as chelating agents. The ex situ remediation method using soil box successfully demonstrated that nitric acid which attracted artificial contaminated zinc had been precipitated at the vicinity of cathode terminal in a form of reddish layer. In conclusion, nitric acid is highly recommended as solution for enhancing electroosmosis process.